Hyponatremia after neuroendoscopic skull base tumor surgery: Clinical characteristics and nursing management - Yang, Yanjun; Lv, Chunmei; Zhang, Jing; Zhao, Yuanli (Frontiers in Surgery, 2022)
Purpose The current study was conducted to explore the clinical characteristics of hyponatremia after neuroendoscopic skull base tumor resection, and to summarize the nursing experience and provide insight for nursing management. Methods In total, we enrolled 181 patients who underwent neuroendoscopic resection of skull base tumors in the Department of Neurosurgery of our hospital from 2016 to 2021. The patients' general data and parameters, including blood sodium level, polyuria, and other symptoms in different periods after surgery, were retrospectively reviewed. Results Forty-four patients developed hyponatremia after Surgery. The total incidence of hyponatremia was 24.30%, including 38 cases of mild hyponatremia and 6 cases of moderate and severe hyponatremia. Most cases of moderate and severe hyponatremia occurred 6 days after surgery. The incidence of hyponatremia varied in different pathological types and periods in patients undergoing skull base tumors. After standardized sodium supplementation, water restriction, and urine volume control, hyponatremia was corrected in all patients, and no osmotic demyelination syndrome (ODS) and nursing-related events occurred. Conclusion Secondary hyponatremia after neuroendoscopic resection of skull base tumors can occur in various time periods after surgery. Early monitoring of manifestations and standardized intervention are thus necessary for clinical nursing practice to timely correct hyponatremia and avoid demyelination.